Built to lie: Investigating technologies of deception, surveillance, and control. Issue 4 (7th August 2016) - Monahan, Torin
ABSTRACT: This article explores technological systems that dissimulate by design. Examples include untrustworthy hotel and workplace thermostats, digital applications to spy on workers and family members, and commercial and law-enforcement systems that surreptitiously collect mobile phone data. Rather than view such cases as exceptional, I argue that deceptive communication systems are hidden articulations of normal technological orders. If deception in itself is not the primary problem with such systems, then transparency alone cannot be the solution. As troubling as institutional opacity might be, an analysis of deceptive systems reveals more fundamental problems: imbalances in power and widespread acquiescence to corporate and state efforts to control individuals, groups, and their data. By moving beyond a quest for (or belief in) technological veracity, scholars could redirect attention to power inequalities and the pressing question of how to live together ethically.